2013
DOI: 10.5194/acpd-13-21259-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Saharan dust aerosol over the central Mediterranean Sea: optical columnar measurements vs. aerosol load, chemical composition and marker solubility at ground level

Abstract: This study aims at the determination of the mineral contribution to PM10 in the central Mediterranean Sea on the basis of 7 yr of PM10 chemical composition daily measurements made on the island of Lampedusa (35.5° N, 12.6° E). Aerosol optical depth measurements are carried out in parallel while sampling with a multi-stage impactor, and observations with an optical particle counter were performed in selected periods. Based on daily samples, the total content and soluble fraction of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…During the AIRUSE campaign, a maximum value about 20 lg/m 3 was reached, corresponding to approximately 60% of the PM10 mass, while in days not affected by Saharan dust, the concentration of the crustal component was only few lg/m 3 . Detailed examples of this approach are reported in [9,30,31].…”
Section: Mineral Dustmentioning
confidence: 99%
“…During the AIRUSE campaign, a maximum value about 20 lg/m 3 was reached, corresponding to approximately 60% of the PM10 mass, while in days not affected by Saharan dust, the concentration of the crustal component was only few lg/m 3 . Detailed examples of this approach are reported in [9,30,31].…”
Section: Mineral Dustmentioning
confidence: 99%
“…The same studies [34,36] identified nanoparticles of compounds resulting from reactions of their components with anthropogenic aerosols, especially ammonium sulphate (NH 4 HSO 4 ). Samples collected at high altitudes were associated with air masses coming from Europe and travelling over North African desert areas.…”
Section: Desert Surfaces Of the Planetmentioning
confidence: 99%